(untitled) (Eurasian Scientific Herald, 2022)
Gossypol itself and its derivatives are currently used in medical practice as a means against viral diseases, as they have a wide range of physiological activity. Schiff bases with heterocyclic amino compounds of gossypol, and water-soluble supramolecular complexes were obtained and their structure was studied using the IR, -UB, and -PMR spectra.